A study on the effectiveness of safety and health at workplace: case Of National Institute Occupational Safety and Health (NIOSH) Bintulu/ Nurul Farhana Matamit - Matamit, Nurul Farhana (2015)
This research study analyzed the information regarding on how effective safety course (confined space) provided by NIOSH Bintulu among the participants. Confined space is one of occupation that very known in construction or manufacturing industry. In Bintulu, most of the industries need workers in confined space field. There was no research that gathers the information about how confined space course in NIOSH could influence the workers at workplace. The purpose of this study was to measure the effectiveness of confined space course in NIOSH Bintulu to be applied by workers at workplace. The results of the study will give advancement in upgrading safety and health awareness at workplace among its participants. It also would assist them in providing information on how confined space course could affect workers’ safety and health at their workplace, explaining on how a healthy workplace can influence mental, physical health, safety and behavior of workers.